THE PREGNANCY PLANNING IN WOMEN WITH MOOD DISORDER - Nurul Fathiyyah (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Background: Pregnancy in women with mood disorder can affect the progress of the pregnancy itself and their fetus, not only came from the medication (due to teratogenicity impact) but also from the mood disorder itself. Planning and preparation for this special population need to be full evaluating to minimize the risk of relapse or rising of emergency psychiatric situation.Objective: to reveal about planning preconception based on review.Method: this paper used to review topic about pregnancy preparation in women with mood disorders.Results: Pregnancy planning in women with mood disorder need to be monitored well from the family planning itself by birth control,supplementation before conception, calculate about risk and benefit of medication, application of health life style and counseling. Activation of Consultation liaison psychiatry needed to controlled about their mental condition concisely.Conclusion: Women with mood disorder need to prepared much more than general population which involved on family planning, understanding the benefit and risk about medication in heavy comorbidities. Keywords: planning, pregnancy, mood disorder.